A hydrological drought risk assessment method based on a four-dimensional Copula function model integrating development and recovery speed characteristics - Xiangyang Zhang; Zening Wu; Huiliang Wang; Zhilei Yu; Yifan Chen (Ecological Indicators, 2025)
Global warming has increasingly exacerbated drought issues, and complex hydrological droughts cause substantial damage across multiple societal systems. Univariate or traditional drought characteristics may be insufficient to reflect the multidimensional nature of drought events. Furthermore, more emphasis should be placed on the probability of the drought phenomenon and its initial impacts in drought risk assessment. This study focuses on hydrological droughts and introduces two new characteristic variables—drought development speed (DS) and recovery speed (RS)—based on duration (D) and severity (S). A four-dimensional hydrological drought risk assessment model is proposed, where these characteristic variables are treated as the loss and are coupled with occurrence probability using a Copula function. The model is used to study hydrological droughts in the Yellow River Basin (YRB) from 1960 to 2018. The results demonstrate that: (1) The model can effectively capture drought conditions in the YRB, where runoff generally declined by up to 13%. The frequency of hydrological droughts ranges from 0.31 to 0.39, with mild and moderate droughts accounting for 82–96%. (2) D, S, and DS exhibited intensification trends (0.0089/a, −0.0213/a, and −0.0043/a, respectively), whereas RS shows an alleviation trend (0.0028/a). (3) The four-dimensional Copula function is predominantly a Gaussian Copula function. Hydrological drought risks show a slowly intensification trend of 0.0004/a, with higher risk values in the upper and middle reaches. This study provides a new perspective for quantifying the multidimensional characteristics of droughts and assessing hydrological drought risks in large basins.